PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN WEBSITE GOOGLE SITES PADA KELAS V B UPT SDN 05 PASAR BARU KABUPATEN PESISIR SELATAN - Nurani, Intan; Hamimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted in response to the low achievement of students in IPAS learning in class V B at UPT SDN 05 Pasar Baru, where 68.75% of students did not meet the minimum mastery standard. The study aims to describe the stages of planning, implementation, and the improvement of learning outcomes through the application of the Problem Based Learning (PBL) model supported by Google Sites as a digital platform. The research design used was Classroom Action Research (CAR) based on the Kemmis and McTaggart cycle model, implemented in two cycles. Each cycle consisted of planning, action, observation, and reflection. The participants involved were 16 students. Data were collected through observation, documentation, and learning outcome tests. The findings reveal that the integration of PBL with Google Sites effectively enhances students’ learning outcomes. The level of student mastery increased from 31.25% in the preliminary stage to 87.5% in the second cycle. Therefore, it can be concluded that the PBL model assisted by Google Sites is effective in improving IPAS learning outcomes at the elementary school level.